Kinetics of human sperm acrosomal exocytosis - Sosa, Claudia Marcela (2014)
The acrosome reaction is a unique event in the lifespan of sperm characterized by the exocytosis of the acrosomal content and the release of hybrid vesicles formed by patches of the outer acrosomal membrane and the plasma membrane. This unique regulated exocytosis is mediated by essentially the same membrane fusion machinery present in neuroendocrine cells. However, whereas secretion in neuroendocrine cells occurs in less than a second, the acrosome reaction is normally assessed after several minutes of incubation with inducers. In this report, we measured the kinetics of human sperm exocytosis triggered by two stimuli (calcium ionophore and progesterone) by using electron microscopy and three different approaches based on the incorporation of fluorescent Pisum sativum agglutinin into the acrosome upon opening of fusion pores connecting the extracellular medium with the acrosomal lumen. The results with the different methods are consistent with a slow kinetics (t1/2 = 14 min). We also manipulated the system to measure different steps of the process. We observed that cytosolic calcium increased with a relatively fast kinetics (t1/2 = 0.1 min). In contrast, the swelling of the acrosomal granule that precedes exocytosiswas a slow process (t1/2 = 13 min). Whenswelling wascompleted, the fusion pore opening wasfast (t1/2 = 0.2 min). The results indicate that acrosomal swelling is the slowest step and it determines the kinetics of the acrosome reaction. After the swelling is completed, the efflux of calcium from intracellular stores triggers fusion pores opening and the release of hybrid vesicles in seconds.